Nutrient-cycling microbes in coastal Douglas-fir forests: regional-scale correlation between communities, in situ climate, and other factors - Shay, Philip-Edouard; Winder, Richard S.; Trofymow, J. A. (Frontiers in Microbiology, 2015)
Microbes such as fungi and bacteria play fundamental roles in litter-decay and nutrient-cycling; however their communities may respond differently than plants to climate change. The structure (diversity, richness and evenness) and composition of microbial communities in climate transects of mature Douglas-fir stands of coastal British Columbia rainshadow forests was analysed, in order to assess in situ variability due to different temperature and moisture regimes. We compared DGGE profiles of fungi (18S-FF390/FR1), nitrogen-fixing bacteria (NifH-universal) and ammonia-oxidizing bacteria (AmoA) PCR amplicons in forest floor and mineral soil samples from three transects located at different latitudes, each transect spanning the Coastal Western Hemlock and Douglas-fir biogeoclimatic zones. Composition of microbial communities in both soil layers was related to degree days above 0°C (2725 - 3489), while pH (3.8 - 5.5) best explained shifts in community structure. At this spatial scale, climatic conditions were likely to directly or indirectly select for different microbial species while local site heterogeneity influenced community structure. Significant changes in microbial community composition and structure were related to differences as small as 2.47% and 2.55°C in mean annual moisture and temperature variables, respectively. The climatic variables best describing microbial composition changed from one functional group to the next; in general they did not alter community structure. Spatial distance, especially associated with latitude, was also important in accounting for community variability (4 - 23%); but to a lesser extent than the combined influence of climate and soil characteristics (14 - 25%). Results suggest that in-situ climate can independently account for some patterns of microbial biogeography in coastal Douglas-fir forests. The distribution of up to 43% of nutrient-cycling microorganisms detected in forest soils responded to smaller abiotic gradients than host trees.